Fructose-induced metabolic reprogramming of cancer cells - Ting, Kenneth K. Y. (Frontiers in Immunology, 2024)
Excess dietary fructose consumption has been long proposed as a culprit for the world-wide increase of incidence in metabolic disorders and cancer within the past decades. Understanding that cancer cells can gradually accumulate metabolic mutations in the tumor microenvironment, where glucose is often depleted, this raises the possibility that fructose can be utilized by cancer cells as an alternative source of carbon. Indeed, recent research has increasingly identified various mechanisms that show how cancer cells can metabolize fructose to support their proliferating and migrating needs. In light of this growing interest, this review will summarize the recent advances in understanding how fructose can metabolically reprogram different types of cancer cells, as well as how these metabolic adaptations can positively support cancer cells development and malignancy.The daily consumption of fructose per person in United States has increased by 26% since the 1970s, highly correlating with the rise of incidence in obesity, metabolic diseases (ex. type 2 diabetes mellitus and non-alcoholic fatty liver disease (NAFLD)), neurological dysfunction and various types of cancer (4-7). This consequentially prompted the launch of many studies to determine if a TME enriched with high levels of fructose can reprogram cancer cells, enabling them to utilize fructose as a secondary source of fuel. As expected, an increasing number of studies have now shown that various types of cancer cells can indeed oxidize TME-derived fructose to support their proliferative and migrative needs, and these discoveries have been summarized in the following sections.